High-Mobility Multipurpose Wheeled Vehicle Rollover Accidents and Injuries to U.S. Army Soldiers by Reported Occupant Restraint Use, 1992–2013. Issue 5 (1st May 2017) - Lo, Michael C.; Giffin, Robert P.; Pakulski, Kraig A.; Davis, W. Sumner; Bernstein, Stephen A.; Wise, Daniel V.
ABSTRACT: Objective: The high-mobility multipurpose wheeled vehicle (HMMWV) is a light military tactical vehicle. During Operation Iraqi Freedom and Operation Enduring Freedom, the U.S. Army modified the HMMWV into a combat vehicle by adding vehicle armor, which made the vehicle more difficult to control and more likely to roll over. Consequently, reports of fatal rollover accidents involving up-armored HMMWVs began to accumulate during the up-armoring period (August 2003 to April 2005). Furthermore, the lack of occupant restraint use prevalent in a predominantly young, male, and enlisted military population compounded the injuries resulting from these accidents. In this retrospective case series analysis, we describe the characteristics of U.S. Army HMMWV rollover accidents, occupants, and injuries reported worldwide from fiscal year 1992 to 2013 based on reported occupant restraint use. Methods: We conducted all analyses using Microsoft Excel 2010 and SAS version 9.1. Because this analysis does not constitute human subjects research, no institutional review board review was required. First, we obtained U.S. Army HMMWV accident records from the U.S. Army Combat Readiness Center, and selected those records indicating a HMMWV rollover had occurred. Next, we successively deduplicated the records at the accident, vehicle, occupant, and injury levels for descriptive analysis of characteristics at each level. For each occupant position, we calculated relative, attributable, and population attributable risks of nonfatal and fatal injury based on reported occupant restraint use. Finally, we analyzed body part injured and nature of injury to characterize the injury patterns that HMMWV occupants in each position sustained based on restraint use. We performed a χ 2 test of homogeneity to assess differences in injury patterns between restrained and unrestrained occupants. Results: A total of 819 U.S. Army HMMWV rollover accidents worldwide were reported from October 1991 through May 2013 involving 821 HMMWVs and 1, 395 occupants (828 nonfatally injured, 151 fatally injured, and 416 noninjured). Thirty-five percent of more severe (class A and B) accidents involved the M1114 up-armored variant, whereas 32% of less severe (class C and D) accidents involved the M998 nonarmored variant. Unrestrained occupants were 20% more likely to be nonfatally injured and 5.6 times more likely to be fatally injured than were restrained occupants. Among unrestrained occupants, restraint use could have potentially saved 82% of lives lost. Among all occupants involved in a HMMWV rollover, an estimated 56% of fatalities could have been prevented by restraint use. Unrestrained drivers and vehicle commanders had greater than expected torso injuries, while restrained vehicle commanders and passengers had greater than expected upper extremity injuries. Unrestrained drivers had greater than expected fractures, whereas restrained drivers and vehicle commanders had greater than expected sprains/strains. Conclusion: While reporting bias may exist, nevertheless these results show that occupant restraint use confers substantial life-saving protection to HMMWV occupants in rollover accidents. Therefore, commanders, safety officers, and peers should continue to promote and enforce restraint use consistently during all Army ground operations and training involving HMMWVs. Doing so will save Soldiers' lives in rollover accidents during the remaining years of the HMMWV program.